2020
DOI: 10.3390/ijms21165669
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Efficacy of the Herbal Recipe Benja Amarit against Highly Invasive Cholangiocarcinoma by Inducing Apoptosis both In Vitro and In Vivo

Abstract: Thailand is the country with highest incidence and prevalence of cholangiocarcinoma (CCA) in the world. Due to the frequently late diagnosis that is associated with this disease, most CCA patients are prescribed chemotherapy as a form of treatment. However, CCA is able to resist the presently available chemotherapy, so to the prognosis of this disease is still very poor. In this study, we investigated the anticancer potential of a Thai herbal recipe, Benja Amarit (BJA) against CCA and the relevant mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The activation of autophagy depends on the duration of treatment. Autophagy is induced over a short period of treatment time, whereas apoptosis is activated over a longer period of treatment time [ 35 ]. Since calomelanone increased HepG2 cell viability at 24 h, the investigation of whether calomelanone induced HepG2 cell survival via the autophagy-mediated mechanism was performed by HepG2 cell treatment at various concentrations of IC values over 48 h but over a shorter incubation period (24 h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of autophagy depends on the duration of treatment. Autophagy is induced over a short period of treatment time, whereas apoptosis is activated over a longer period of treatment time [ 35 ]. Since calomelanone increased HepG2 cell viability at 24 h, the investigation of whether calomelanone induced HepG2 cell survival via the autophagy-mediated mechanism was performed by HepG2 cell treatment at various concentrations of IC values over 48 h but over a shorter incubation period (24 h).…”
Section: Resultsmentioning
confidence: 99%
“…At 24 h, the IC values could not be determined due to the proliferation character of HepG2 cells in response to calomelanone. Monodansylcadaverine (MDC) is a specific fluorescence dye for autophagosomes, autophagolysosomes, or autophagic vacuoles, representing the functional autophagic flux [ 35 , 36 ]. Stained cells, both cell morphology (qualitatively) and quantitatively positive stained cells, were examined under fluorescence microscopy and by flow cytometry, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis, formerly also called programmed cell death (PCD), [15] has been widely proved to be a major type of cell death to suppress cancer development. Therefore, induction of apoptosis is considered to be a potential antitumor strategy [16] . Overexpression of Bcl‐2 has been identified in numerous cancers [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Costantini et al showed that the hydroxytyrosol contained in olive oil ( Olea europea ) induces the apoptotic death of melanoma cells by increasing ROS levels, p53 and γH2AX expression and by the decrease in AKT expression [ 3 ]. A Thai herbal preparation known as Benja Amarit is capable of inducing apoptotic death in cholangiocarcinoma cells, through the regulation of the nuclear factor-KB (NF-KB) signaling pathway [ 4 ]. Both hydroxytyrosol and Benja Amarit preparation result in safe and promising therapeutic tools for the treatment of these highly invasive tumors.…”
mentioning
confidence: 99%